Torakochirurgia Significance of frozen section investigation for pulmonary lesions and bronchial margins resection - Langfort, Renata (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2007)
The frozen section (FS) examination is one of the most difficult histopathological procedures. It requires a lot of experience from the pathologist and good cooperation between surgeon and pathologist. The main reasons for performing FS are: to establish the presence and nature of a lesion, to determine the adequacy of surgical resection margins, and to establish whether the tissue obtained contains enough diagnosable material for microscopic examination. Other indications pertaining to lung pathology and lung-related lesions include evaluation of lung cancer staging and a confirmation by tissue diagnosis of a specimen obtained previously by fine-needle aspiration, core-needle biopsy, or bronchoscopy, cytology or biopsy, especially when histopathological diagnosis raises clinical doubts. Most FS diagnoses are in accordance with the definitive results. A small number of FS are postponed and a final diagnosis is based on paraffin section. However, a false-negative or false-positive FS arising from incorrect diagnosis may happen. False-negative FS include both errors of sampling and errors of interpretation. False-positive FS include incorrect microscopic diagnosis of malignancy. An understanding of indications for FS, diagnostic possibilities, limitations and difficulties of this procedure are a very important element of cooperation between the surgeon and surgical pathologist.